PENGEMBANGAN MEDIA PEMBELAJARAN FRACTION FUN BOX (FFB) REALISTIC MATHEMATIC PADA MATA PELAJARAN MATEMATIKA MURID KELAS II SDN 1 BUKUR KABUPATEN TULUNGAGUNG - Prasetyani, Silvia Febriana; Ana, Ria Fajrin Rizqy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics is an abstract subject; therefore, elementary school students need concrete and interesting learning media to help them understand learning concepts more easily, especially on simple fraction material. This study aimed to develop Fraction Fun Box (FFB) learning media based on Realistic Mathematics for simple fraction material in the second grade of elementary school. The research method used was Research and Development (R&D) with the ADDIE model consisting of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were 15 second grade students of SD Negeri II Bukur. The results of the study showed that the first material expert validator obtained a percentage score of 98% with a very valid category, while the second material expert validator obtained a percentage score of 96% with a very valid category. The media expert validation obtained a percentage score of 96% with a very valid category. Based on the teacher response questionnaire, the percentage score obtained was 95% with a very good category, while the students’ response questionnaire obtained a percentage score of 92% with a very good category. Based on these results, it can be concluded that the Fraction Fun Box (FFB) learning media based on Realistic Mathematics in mathematics subject for second grade students is highly valid to be implemented for second grade students at SDN 1 Bukur.